2021
DOI: 10.1111/pce.14060
|View full text |Cite
|
Sign up to set email alerts
|

Leaf heat tolerance of 147 tropical forest species varies with elevation and leaf functional traits, but not with phylogeny

Abstract: Exceeding thermal thresholds causes irreversible damage and ultimately loss of leaves. The lowland tropics are among the warmest forested biomes, but little is known about heat tolerance of tropical forest plants. We surveyed leaf heat tolerance of sun‐exposed leaves from 147 tropical lowland and pre‐montane forest species by determining the temperatures at which potential photosystem II efficiency based on chlorophyll a fluorescence started to decrease (TCrit) and had decreased by 50% (T50). TCrit averaged 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
71
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 78 publications
13
71
2
Order By: Relevance
“…We note that the PHT thresholds observed in the current study are in the lower end of the range reported for tropical tree species: for T crit from c. 46-50°C, and for T 50 from c. 44.5-53°C (e.g. Sastry & Barua, 2017;Zhu et al, 2018;Feeley et al, 2020;Tiwari et al, 2021;Slot et al, 2021). Given that our laboratory-based measurements on Hmo also yielded higher threshold values in the higher temperature treatments (i.e.…”
Section: Observed Photosynthetic Heat Tolerance Thresholds Compared To Previous Studiessupporting
confidence: 42%
“…We note that the PHT thresholds observed in the current study are in the lower end of the range reported for tropical tree species: for T crit from c. 46-50°C, and for T 50 from c. 44.5-53°C (e.g. Sastry & Barua, 2017;Zhu et al, 2018;Feeley et al, 2020;Tiwari et al, 2021;Slot et al, 2021). Given that our laboratory-based measurements on Hmo also yielded higher threshold values in the higher temperature treatments (i.e.…”
Section: Observed Photosynthetic Heat Tolerance Thresholds Compared To Previous Studiessupporting
confidence: 42%
“…There are growing interests to understand the underlying causes behind the variation in intrinsic and/or acquired P T . Different leaf structural and biochemical factors were attributed to the variation in P T including the leaf mass per unit area (Sastry & Barua, 2017; Slot et al, 2021), leaf thermoregulatory traits (Perez & Feeley, 2020), abundance of cellular heat‐shock proteins (Barua et al, 2008) and saturated fatty acids (Zhu et al, 2018), foliar Ca concentration (Zhang et al, 2012) and epicuticular wax load (Tischler & Burson, 1995). Studies that investigated intraspecific or genotypic variation in P T predominantly come from model crop systems (Cottee et al, 2010; Hall et al, 2014), some herbaceous crop species (Barua et al, 2008), and few agroforestry tree species (Gomes‐Laranjo et al, 2006; Gomes‐Laranjo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are growing interests to understand the underlying causes behind the variation in intrinsic and/or acquired P T . Different leaf structural and biochemical factors were attributed to the variation in P T including the leaf mass per unit area (Sastry & Barua, 2017;Slot et al, 2021), leaf thermoregulatory traits , abundance of cellular heat-shock proteins (Barua et al, 2008) and saturated fatty acids (Zhu et al, 2018), foliar…”
Section: Npq Increased With Warming Intensity and Even Remained High ...mentioning
confidence: 99%
“…Carbon balance can be viewed as a push-pull dynamic that is driven by mitochondrial respiration and pho- considered a limiting factor in the ability to maintain photosynthesis under high temperatures, an idea that is explored by Perez, Socha, Tserej, and Feeley (2021) and . Perez et al (2021) found that high heat tolerance of PSII was associated with species that were thermal generalists, thus providing a proxy for evaluating the thermal niche of plants, while Slot, Cala, et al (2021) showed that PSII heat tolerance varies in a predictable way with site temperature and elevation. The ability to acclimate CO 2 uptake rates to higher temperatures is often related to shifts in the thermal sensitivity and capacity of photosynthetic processes, and can occur quite quickly (Slot, Rifai, & Winter, 2021).…”
Section: Carbon Dynamics As a Key Regulator Of Plant Heat Stress Responsesmentioning
confidence: 99%